INFORMASI DESTINASI WISATA BERBASIS PETA GOOGLE: STUDI KASUS KABUPATEN GUNUNGKIDUL - Wasino, Wasino; Dewayani, Ery; Arisandi, Desi; Andanwerti, Noeriatri (Jurnal Teknologi Terapan, 2019)
In Gunungkidul district, there are many tourist destinations that are worth visiting and have become tourist destinations from various regions outside Gunungkidul district. The context of the problem that underlies this research is the growing interest in developing applications through online map services using Google maps. The purpose of building a google map-based tourist destination information application is to make it easier for tourists to get tourist destination information through an integrated map with the web. The method used to gather needs and analysis is a fact-finding method with conducting unstructured interviews. The author also made direct observations on the spot, this method is very effective for analyzing and discovering system functions and gaining direct knowledge about activities, operations, and processes. The results of this study are database design that has been normalized to the 3rd normal form, and the application of travel information on Google maps. Through functional testing, this application has run well using travel data taken directly in Gunungkidul district.